2005
DOI: 10.1016/j.dss.2004.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Can we prevent the gaming of ramp constraints?

Abstract: Some electric power markets allow bidders to specify constraints on ramp rates for increasing or decreasing power production. We show in a small example that a bidder could use an overly restrictive constraint to increase profits, and explore the cause by visualizing the feasible region from the linear program corresponding to the power auction. We propose two penalty approaches to discourage bidders from such a tactic: one based on duality theory of Linear Programming, the other based on social cost differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 5 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…A number of studies, including [16] and [17], have demonstrated potential incentive issues with generators being able to profitably misstate their cost and constraint parameters when offering generation into a centrally-committed market. If one expects the exercise of market power to increase real-time prices, perhaps disproportionately in peak periods when supply is scarce, then our simulations may underestimate the extent to which RTP could flatten peaks and affect the load pattern.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies, including [16] and [17], have demonstrated potential incentive issues with generators being able to profitably misstate their cost and constraint parameters when offering generation into a centrally-committed market. If one expects the exercise of market power to increase real-time prices, perhaps disproportionately in peak periods when supply is scarce, then our simulations may underestimate the extent to which RTP could flatten peaks and affect the load pattern.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong body of research that studies the design and implementation of auctions in these markets looking at various aspects, such as bidding behavior, computation of market clearing prices, and the efficiency of the resulting dispatch (e.g., Derinkuyu , Elmaghraby , Madani and Van Vyve , Meeus et al. , Oren and Ross , Pritchard and Philpott , Reguant , , Schummer and Vohra , Singer , Toczy lowski and Zoltowska ).…”
Section: Electric Power Industry Research Frontier and Potential Resementioning
confidence: 99%
“…Ruff (1994), Hogan (1994), Hogan (1995), Hunt (2002) support centrally committed markets because they give the SO, which has the best information about the electric system as a whole, the authority to make both commitment and dispatch decisions. However, Oren and Ross (2005) show that generators can have incentives to misstate their costs to increase profit if the SO collects multipart bids. Moreover, Johnson et al (1997), Sioshansi et al (2008) claim that incentive compatibility issues in a centrally committed market can be further exacerbated if the SO must rely on suboptimal solutions to its unit commitment model.…”
Section: Introductionmentioning
confidence: 97%